2012
DOI: 10.4253/wjge.v4.i5.157
|View full text |Cite
|
Sign up to set email alerts
|

Management of an occluded biliary metallic stent

Abstract: In patients with a malignant biliary obstruction who require biliary drainage, a self-expandable metallic stent (SEMS) provides longer patency duration than a plastic stent (PS). Nevertheless, a stent occlusion by tumor ingrowth, tumor overgrowth and biliary sludge may develop. There are several methods to manage occluded SEMS. Endoscopic management is the preferred treatment, whereas percutaneous intervention is an alternative approach. Endoscopic treatment involves mechanical cleaning with a balloon and a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Ridtitid et al found no difference in the duration of patency between a PS and SEMS placed in a "stent-in-stent" manner (60 days in each case); however, the duration of patency was relatively short in both cases [22]. PTBD is an alternative intervention when endoscopic management fails, particularly where the desired intrahepatic duct is endoscopically inaccessible following bilateral SEMS insertion for hilar [23]. The main disadvantages of PTBD are pain, inconvenience, and volume/electrolyte loss.…”
Section: Discussionmentioning
confidence: 99%
“…Ridtitid et al found no difference in the duration of patency between a PS and SEMS placed in a "stent-in-stent" manner (60 days in each case); however, the duration of patency was relatively short in both cases [22]. PTBD is an alternative intervention when endoscopic management fails, particularly where the desired intrahepatic duct is endoscopically inaccessible following bilateral SEMS insertion for hilar [23]. The main disadvantages of PTBD are pain, inconvenience, and volume/electrolyte loss.…”
Section: Discussionmentioning
confidence: 99%
“…of hospitalization, lower overall costs, and lower morbidity; however, maintenance of stent patency is difficult because of tumor ingrowth or overgrowth. 5,6 Tissue ablation techniques such as radiofrequency ablation (RFA) can safely induce tumor necrosis and are successfully used in early stage cancers or patients unfit for surgery. Recently, endoscopic or percutaneous focal ablation has been piloted to prolong ductal patency and debulk ingrowing tumors.…”
mentioning
confidence: 99%
“…Different stent patency and survival time from previous studies may be explained by differences in stent material as well as patient selection and the duration of follow up. Recent review paper concluded that the appropriate management of occluded SEMS is still unclear and controversial . They concluded that endoscopic insertion of SEMS or plastic stent is equally effective for SEMS occlusion in a patient with short survival and another SEMS insertion is preferred in a patient with longer survival.…”
Section: Discussionmentioning
confidence: 99%